Smallholder Oil Palm Farming Based on ISPO Certification: Sustainable or Not? - Mirawati Yanita; Gina Fauzia; Rozaina Ningsih; Dompak MT Napitupulu; Karina Rahmah; Ulidesi Siadari; Zulkifli Alamsyah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Oil Palm farming has a substantial positive impact on job creation and the socio-economic conditions of communities, particularly in rural areas. However, a major challenge faced by smallholder Oil Palm farmers, especially those operating on a small scale, is the sustainability of their farming practices. These barriers often hinder the implementation of sustainable agricultural practices that align with certification standards, particularly the Indonesian Sustainable Oil Palm (ISPO) standards. This study aims to describe the social and economic characteristics of ISPO-certified smallholder Oil Palm farmers, analyze management practices based on farm performance, and assess the sustainability model of smallholder Oil Palm farming in Merangin Regency, as reflected in ISPO certification. The research was conducted in Nalo Tantan District, which has varying levels of Oil Palm productivity and ISPO-certified smallholder farmers. The study used observational methods, direct interviews, and secondary data analysis from relevant institutions and scientific literature. A sample of 60 respondents was selected for the study. The results showed an average Oil Palm production of 84.43 tons/ha/year with an average selling price of IDR 2,682/kg. The average land area used by farmers was 3.40 ha, with fertiliser use of 840 kg/ha/year and pesticide use of 7.1 liters/ha/year. The sustainability analysis showed that ISPO-certified smallholder Oil Palm farming in Nalo Tantan has a relatively good sustainability status, with a sustainability index of 66.99. The economic dimension was highly sustainable with a score of 77.85, while the social and ecological dimensions were moderately sustainable, scoring 57.76 and 67.22, respectively. It is crucial to strengthen certification implementation, improve social and environmental management, and support economic sustainability by enhancing resource management and expanding market access.